Seroprevalence study of infectious laryngotracheitis virus antibody of commercial layer in Gazipur Districts of Bangladesh - Rahman, Md Mijanur; Uddin, Md Karim; Hassan, Md Zakir; Rahman, Md Mamunur; Ali, Md Zulfekar; Rahman, Md Lutfor; Akter, Mir Rowshan; Rahman, Md Mostafizer (Asian Journal of Medical and Biological Research, 2018)
This research work was conducted to detect the prevalence of Infectious Laryngotracheitis (ILT) Virus-specific antibody in chickens from Gazipur district in Bangladesh at Department of Microbiology, Hajee Mohammad Danesh Science & Technology University, Dinajpur and Poultry Care Lab, Garzipur from January to June 2012. A total number of 232 sera sample of commercial layer chicken were collected from 17 different commercial layer farms at different ages. The layers prognosed for sampling had not been previously vaccinated against ILTV. The indirect enzyme linked immunosorbent assay (iELISA) was performed to estimate the Infectious Laryngotracheitis (ILT) Virus-specific antibody. Out of 232 samples, 189 (81.47%) samples were found to positive for Infectious Laryngotracheitis (ILT) Virus-specific antibody. In 17 different commercial farms prevalence based on age were 75%, 87.5%, 87.5%, 90%, 81.25%, 80%, 100%, 70%, 81.25%, 81.25%, 90%, 93.08%, 87.5%, 75%, 75%, 68.75% and 75% in the age limit 08, 09, 11, 12, 13, 14, 15, 16, 17, 17, 19, 21, 25, 31, 35, 44 and 51 weeks respectively and farms showed high level of ILT virus specific antibodies (IgG). This result showed that in 15 weeks of age prevalence was highest position i.e; 100%. The result of this study indicate that there were a high prevalence of Infectious Laryngotracheitis (ILT) Virus circulating at Gazipur district in Bangladesh. Asian J. Med. Biol. Res. March 2018, 4(1): 1-6